A review of satellite positioning systems for civil engineering - Roberts, Gethin Wyn; Tang, Xu; Brown, Chris (ICE Publishing, 2015)
This paper informs and updates civil engineers of the status and advances of global navigation satellite systems, and how this will affect the profession in the near future. An overview of the various global and regional systems is given. Real data are used to show the potential precision of the US Global Positioning System and other global navigation satellite systems, as well as the advantages of using a multi-system approach. The results illustrate that there is a clear increase in the availability of satellites through a multi-system approach, as well as an improvement in the resulting coordinate precision.